Experimental Study on the Bonding Performance of FFRP Reinforced Timber Interface - Yuanyuan Xia; Qiang Du; Xinyue Zhang; Yangyang Xia; Guijun Xian; Lin Mu; Ningjun Du (Journal of Natural Fibers, 2023)
Although there are lots of researches about the application of FRP composites on the external bonding and reinforcement of timber structures, they are mostly aimed at Carbon FRP, which has a large difference in mechanical properties and inconsistent deformation with timber. Meanwhile, research about the interface between timber and Flax Fiber Reinforced Polymer (FFRP) with similar properties with timber is limited; hence, relevant models have not been established yet. Similar to linear elastic FRP confined timber structure, the failure of FFRP-timber structure interface is a process in which the interfacial stress is gradually transferred from the loaded end to the free end, and the interfacial stress transfer area, that is an effective bond length of the FFRP-timber interface. In order to study the interfacial stress transfer characteristics between FFRP and timber structure, based on the existing CFRP-timber structure interface bonding theory and mechanism, a single lap shear test is used to conduct a systematic study on bonding length and width are studied to optimized the application of FFRP. The bond-slip behavior is studied and fitted to provide theory support for the application of FFRP in the restoration of ancient timber structures.